Polyembolokoilamania with obsessive compulsive and related disorders: A case series - Avik Kumar Layek; Uttam Majumder; Iti Baidya (Indian Journal of Psychiatry)
Polyembolokoilamania is a condition seen in a medical or surgical emergencies where the person, sometimes repetitively, inserts various foreign bodies through body orifices or skin to obtain gratification often associated with background psychiatric diagnoses. We present three cases where one patient with Obsessive Compulsive Disorder (OCD) presented with urethral polyembolokoilamania, one with Excoriation disorder presented with multiple pin-piercing behavior through the skin and one case of OCD presented with anal polyembolokoilamania. Treatment of the underlying Obsessive-Compulsive and Related Disorders curbed such behaviors successfully in all three cases emphasizing the importance of treating background psychiatric disorders in such conditions.